A New Triazine‐Based Covalent Organic Framework for High‐Performance Capacitive Energy Storage. Issue 5 (20th February 2017) - Bhanja, Piyali; Bhunia, Kousik; Das, Sabuj K.; Pradhan, Debabrata; Kimura, Ryuto; Hijikata, Yuh; Irle, Stephan; Bhaumik, Asim
Abstract: The new covalent organic framework material TDFP‐1 was prepared through a solvothermal Schiff base condensation reaction of the monomers 1, 3, 5‐tris‐(4‐aminophenyl)triazine and 2, 6‐diformyl‐4‐methylphenol. Owing to its high specific surface area of 651 m 2 g −1, extended π conjugation, and inherent microporosity, TDFP‐1 exhibited an excellent energy‐storage capacity with a maximum specific capacitance of 354 F g −1 at a scan rate of 2 mV s −1 and good cyclic stability with 95 % retention of its initial specific capacitance after 1000 cycles at 10 A g −1 . The π‐conjugated polymeric framework as well as ionic conductivity owing to the possibility of ion conduction inside the micropores of approximately 1.5 nm make polymeric TDFP‐1 a favorable candidate as a supercapacitor electrode material. The electrochemical properties of this electrode material were measured through cyclic voltammetry, galvanic charge–discharge, and electrochemical impedance spectroscopy, and the results indicate its potential for application in energy‐storage devices. Abstract : Super framework : The new covalent organic framework TDFP‐1 is prepared through a solvothermal Schiff base condensation reaction and shows an excellent energy‐storage capacity with a maximum specific capacitance of 354 F g −1 at a scan rate of 2 mV s −1 and good cyclic stability (95 % retention of its initial specific capacitance after 1000 cycles).